Visual Intelligence in the development of reading comprehesion of third year of BGU students at “Belisario Quevedo” Educative Unit. - Alvear Jiménez, Tania Elizabeth (2021)
The research focused on the study, analysis and application of visual intelligence in the development of reading comprehension of students of third year of BGU at “Belisario Quevedo” Educative Unit, this research has a mix method approach design as well as a qualitative design, since, during the exploration we work with two groups, one control group (30 students) and one experimental group (30 students); both groups were applied a pretest and a posttest. The main objective of this research was the development of reading comprehension in visual learner, therefore the proposal: Graphic organizers strategies handbook to develop reading comprehension was designed and applied; the results showed a significant improvement in the development of reading comprehension skills, the experimental group who received the proposed intervention, showed better results compared to the control group who were instructed with traditional methods. Therefore we can conclude and assert the effectiveness of the use of graphic organizers as a visual strategy for the development of reading comprehension.